Role of Personality and Positive and Negative Affects in Coping Strategies of Nurses: A Cross-Sectional Study - Martos Martínez, África; Molero Jurado, María del Mar; Pérez-Fuentes, María del Carmen; Barragán Martín, Ana Belén; Simón Márquez, María del Mar; Gázquez Linares, José Jesús (Frontiers in Psychology, 2021)
Nurses are exposed to many highly stressful events. Individual variables, such as personality and affective state, have been related to vulnerability to maladaptive coping. Therefore, the objectives of this study were to analyze the relationships between nurses’ personality, positive and negative affect and coping strategies, and to establishing the mediating role of affective state in the relationship between personality and coping. The sample was made up of 1268 Spanish nurses aged 22 to 63 who completed the Coping Strategies Inventory, the Positive and Negative Affect Schedule and the 10-item Big Five Inventory. Descriptive analyses, correlations and mediation models were estimated. The results showed relationships between the Big Five personality factors, positive and negative affect and coping strategies. Negative affect was confirmed as a mediator between personality and less adaptive strategies, and positive affect on positive strategies. This study emphasizes the need to develop actions directed at teaching nurses adequate problem-solving strategies and training them in the ability to assign a different emotional value to complex situation.s